Creating sustainable businesses and careers: analysis of entrepreneurs’ life stories through the lens of career sustainability - Trevisan, Laís Viera; Bandeira, Patrícia Böck; Silva, Eliane Alves da; Scheffer, Angela Beatriz Busato; Pedrozo, Eugênio Ávila (Revista de Administração da UFSM, 2022)
Purpose: This study aimed to analyze how the career-building process of sustainable entrepreneurs occurs from the perspective of sustainable careers and how the influential factors in their career decisions are related to the dimensions and characteristics of sustainable careers. Design/methodology/approach: This is a qualitative study carried out by analyzing three Brazilian entrepreneurs’ life stories. Subsequently, the data were submitted to narrative analysis using the Atlas.ti software and then interpreted using sustainable career’s dimensions and characteristics. Findings: The study corroborates the literature on entrepreneurship, sustainability, and careers, shedding new light on the career decision process of sustainable entrepreneurs from the assumptions of the sustainable career perspective. We identified the emergence of influential categories as a disorienting dilemma, the importance of agency and meaning dimensions and the career coherence with values, quality of life, and self-fulfillment. In addition, sustainable entrepreneurship appears to be in line with the ideals of decent work, allowing for individual well-being, matching life and career values, and long-term employability. Originality: The sustainable career perspective offers an innovative, dynamic, and systemic perspective to understanding the professional trajectories of sustainable entrepreneurs, considering their learning along their trajectory, crossing different social spaces, experiences, and creations, which allow them to improve the adaptability necessary for the sustainability of their careers.